Gold-bearing prospects of the Nizhnegarsky ore-placer node in the Priamur province - V. A. Stepanov; A. V. Melnikov (Известия высших учебных заведений: Геология и разведка, 2023)
Background. The geological structure and gold-bearing capacity of the recently identified Nizhnegarsky potential ore-placer node of the North Bureinsky metallogenic zone of the Priammur province are investigated.Aim. To define the gold-bearing prospects of the Nizhnegarsky potential ore-placer node and to determine its potential for integrated use.Materials and methods. Available publications and stock materials on the geological structure and gold-bearing capacity of the Nizhnegarsky node were analyzed.Results. An independent Nizhnegarsky potential ore-placer node with industrial placers of gold has been identified for the first time. In the southern part of the node, the gold sources are represented by gold-bearing deposits of iron and pyrite ores of early Proterozoic age. In the northern part, the gold sources presumably include the gold-copper-molybdenum-porphyry mineralization of Late Mesozoic age. The gold-bearing prospects of the Nizhnegarsky node in terms of lobe gold are estimated. In addition to gold, the possibility of associated extraction of zircon and ilmenite, some minerals of the platinum group (sperrilite and iridosmines), and scheelite is demonstrated.